CSC119: Fundamentals of Computer Science / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2016)
This course provides the students with an overall view on how a computer stores information, retrieves and manipulates input and output; the major components of the computer, contemporary computing and application software.